Functional abdominal pain disorders in adolescents in Indonesia and their association with family related stress - Hanifah Oswari; Fatima Safira Alatas; Badriul Hegar; William Cheng; Arnesya Pramadyani; Marc Alexander Benninga; Shaman Rajindrajith (BMC, 2019)
Abstract Background Functional abdominal pain disorders (FAPD) have been widely reported as a major group of gastrointestinal disorders across the world. This study describes the prevalence, related factors, symptomatology and its relationship to emotional stress in Indonesian adolescents. Methods This is a cross-sectional study. Adolescents aged 10 to 17 years from nine randomly selected state schools from five districts of Jakarta, Indonesia, were invited to participate. A translated and validated Rome-III self-administered-questionnaire was used to collect data on gastrointestinal symptoms. Data on sociodemographic characteristics, intestinal as well as extra-intestinal symptoms, and exposure to stressful life events were also collected using a separate validated questionnaire. Results A total of 1813 questionnaires were included in the analysis [males 739 (40.8%) mean age of 13.54 years + 0.89]. Of them, 209 children (11.5%) fulfilled Rome III criteria of FAPD. Functional abdominal pain (FAP) was reported as the most prevalent subtype (5.8%), followed by functional dyspepsia (3.3%), irritable bowel syndrome (2%) and abdominal migraine (0.4%). The prevalence was higher in girls (p < 0.05) and those exposed to family-related stressful life events (p < 0.05). They include divorce or separation of parents (adjusted OR 2.55, 95% CI 1.75-3.7, p = < 0.001), death of a close family member (adjusted OR 2.24, 95% CI 1.39-3.59, P = 0.001), and father's alcoholism (adjusted OR 1.94, 95% CI 1.22-3.1, P = 0.005). Conclusions FAPD are common paediatric entities among Indonesian adolescents with a prevalence of 11.5%. FAPD were noted to be higher in girls and adolescents exposed to family-related stressful life events.